An empirical analysis of the representation of lower-order facets of the big five personality dimensions - Greenidge, Dion DaCosta (2013)
In the field of personality psychology there is some consensus among researchers that human personality, at the broadest level, can be described in terms of five fundamental personality dimensions. Universally, these personality dimensions are referred to as the “Big Five” model or the Five Factor Model (FFM) of personality: Extraversion, Conscientiousness, Agreeableness, Emotional Stability versus Neuroticism, and Intellect or Openness to Experience. However, currently, there is little conceptual or empirical consensus about a meaningful taxonomy of lower-order facets that make up each of the Big Five personality factors. This thesis sought to identify a parsimonious and replicable taxonomy of lower-order facets of the Big Five personality factors, and test the lower-order facet structure for construct and criterion-related validity. Based on the US Eugene-Springfield community sample (ESCS) (N =375), Study 1 examined facet scale scores from nine widely used personality inventories using Exploratory Factor Analysis in order to identify a shared overall lower-order structure for each of the Big Five personality domains. Factor analyses of 162 facet scales revealed 29 facets for the Big Five which demonstrated good convergent validity. However, some facets (e.g. traditionalism, peacefulness, trust) showed less clear patterns of discriminant validity, and thus appear to be compound traits or blends of two or more Big Five factors. In Study 2, a new 232-item Big Five instrument, the Hierarchical Personality Assessment Questionnaire (HPAQ), was developed to measure the 29 lower-order facets derived in Study 1. In the development phase of HPAQ, the factor scores for the 29 facets from Study 1 were correlated with the International Item Pool (Goldberg, 1999) in order to generate an initial pool of items. An initial pool of 348 IPIP items to mark the 29 facets was then administered to a large sample of undergraduate and postgraduate students at a University in the English-speaking Caribbean (N = 778) with the intention of choosing 8 items that best marked each of the facets. Additionally, the HPAQ was validated in a second sample of undergraduate and postgraduate students (N = 807) against the NEO-PIR and its psychometric properties were further examined. The development and validation of the HPAQ was a first step in moving towards Study 3. Study 3 investigated the differential criterion-related validity of the 29 HPAQ lower-order facets in the prediction of job performance criteria (task performance, counterproductive work behaviour, and organisational citizenship behaviours). In addition, the incremental validities of the 29 lower-order facets in the prediction of job performance criteria were also examined. Overall, Study 3 found that the 29 lower-order facets demonstrated differential criterion-related validity and provided incremental validity beyond the global Big Five factors in predicting the job performance criteria and vice versa. Overall, this thesis empirically derives an initial taxonomy of lower-order facets of the Big Five personality factors based on nine personality inventories and developed a new Big Five personality instrument to measure explicitly this lower-order facet structure. The theoretical and practical implications of these results, limitations, and suggestions for future research are discussed.